Molecular evidence for antigen drive in the natural history of mantle cell lymphoma - Xochelli, Aliki; Sutton, Lesley-Ann; Agathangelidis, Andreas; Stalika, Evangelia; Karypidou, Maria; Marantidou, Fotini; Lopez, Alba Navarro; Papadopoulos, Giorgos; Šupíková, Jana; Groenen, Patricia; Boudjogra, Myriam; Sundstrom, Christer; et al. (American journal of pathology, 2015)
To further our understanding about antigen involvement in mantle cell lymphoma (MCL), we analyzed the expression levels of activation-induced cytidine deaminase (AID), a key player in B-cell responses to antigen triggering, in 133 MCL cases; assessed the functionality of AID by evaluating in vivo class switch recombination in 52 MCL cases; and sought for indications of ongoing antigen interactions by exploring intraclonal diversification within 14 MCL cases. The AID full-length transcript and the most frequent splice variants (AID-ΔE4a, AID-ΔE) were detected in 128 (96.2%), 96 (72.2%), and 130 cases (97.7%), respectively. Higher AID full-length transcript levels were significantly associated (P < 0.001) with lack of somatic hypermutation within the clonotypic immunoglobulin heavy variable (IGHV) genes. Median AID transcript levels were higher in lymph node material compared to cases in which peripheral blood was analyzed, implying that clonal behavior is influenced by the microenvironment. Switched tumor-derived IGHV-IGHD-IGHJ transcripts were identified in 5 of 52 cases (9.6%), all of which displayed somatic hypermutation and AID-mRNA expression. Finally, although most cases exhibited low levels of intraclonal diversification, analysis of the mutational activity revealed a precise targeting of somatic hypermutation indicative of an active, ongoing interaction with antigen(s). Collectively, these findings strongly allude to antigen involvement in the natural history of MCL, further challenging the notion of antigen naivety.
Keywords: Cytidine Deaminase; B-lymfocyty; Humans; lidé; Immunoglobulin Variable Region; Somatic Hypermutation, Immunoglobulin; somatická hypermutace imunoglobulinových genů; lymfom z plášťových buněk; Lymphoma, Mantle-Cell; cytidindeaminasa; B-Lymphocytes; variabilní oblast imunoglobulinu